Component commonality in multistage production system: Models with capacity constraints - Wazed, M.A. (2009)

(untitled)
Common components are used extensively for production postponement, reduction of proliferated product lines cost, reduction of the cost of safety stock, increase productivity, improve flexibility, expediting new product development and so on. The authors consider a multistage assemble-to-order system with two products have uniformly distributed demand, one common component and product-specific components. We develop optimization models for minimizing the level of inventory of the components and allocated to products to meet capacity limitation. A numerical example is used to verify and compare the models with similar models.